Dietary acculturation among Filipino Americans rationale for the cultural food choices - Narciso, M. H. (Compendium of Human Ecology Researches in the Philippines, 2003)
This paper investigated dietary acculturation among Filipino-Americans in United States of America through their a) perceptions of meals; b) food procurement and preparation practices; and c) motivations and tendencies for cultural food choice and consumption. It attempted to explain the changes in meal patterns observed utilizing concepts of food availability and the changing meanings and uses of food. There were 267 subjects, they were predominantly females (67 percent), middle aged (median age = 47), highly educated and stayed in the US for a median of 17 years. The Filipino-Americans studied appear to have adopted a bicultural set of food patterns. The discussions reiterated the need for food preparation skills and value formation.